The Garbhagriha (sanctum sanctorum) of the Mahakal Temple - Temples of India Project Team (Jio Institute, 2024)
The garbhagriha (sanctum sanctorum) of the Mahakal Temple on the east is a square, simple, dimly lit chamber which has a Shiva linga at the center. The Mahakal Temple is a living temple where people come to worship regularly Shiva lingas in both the garbhagrihas (east and south).